Access to Affordable and Low-Income Housing in East Asia and the Pacific - World Bank (Washington, DC, 2015)
Across the world, the housing sector plays a key role in local and national economies, and expanding access to housing can encourage more equitably shared economic growth. This report surveys current policy interventions designed to encourage affordable housing in East Asia and the Pacific (EAP). The purpose of this report is to provide a general overview of the recent trends in urbanization and development in EAP and to consider different forms of government, market, and nonprofit actions that support housing affordability. It will also highlight key constraints and barriers that restrict the provision of low-cost housing in urban areas. Housing is important because it represents a significant household expenditure. The report assesses the strengths and limitations of affordable housing strategies used by different countries throughout EAP. This report offers broad conclusions that account for the broad social, political, and institutional variation among EAP countries; as such, these conclusions may well be applicable to more than one country context. The report also provides specific recommendations for improvement where existing interventions are new or have proven less successful. The report is divided into following chapters: chapter one gives introduction. Chapter two examines trends in urbanization rates, economic development, and inequality in order to introduce the need for high-quality, low-cost housing options. Chapter three examines EAP regional trends in urban housing affordability for owners and renters from select cities. Chapter four outlines future directions for affordable housing provision based on a comparative consideration of international best practices. Finally, chapter five surveys different affordable housing policies currently in place in EAP and summarizes their strengths and weaknesses.